Peran Digital Forensik dalam Upaya Melacak Hasil Tindak Pidana Korupsi yang diubah dalam Bentuk Bitcoin - Riyanto Riyanto; Handar Subhandi Bakhtiar (Presidensial: Jurnal Hukum, Administrasi Negara, dan Kebijakan Publik, 2024)
The rapid development of technology has facilitated daily human activities, one of which is the existence of digital financial systems for transactions and investments, with Bitcoin being one of the products of digital currency. The purpose of this research is to carefully examine and analyze the role of digital forensics in efforts to trace the proceeds of corruption crimes that have been converted into Bitcoin. The legal research method used is a normative juridical approach, conducting research on library materials and utilizing the Statute Approach and Case Approach. The results of the research conclude that digital forensics is an important process in legal investigations involving the identification, collection, analysis, and preservation of digital evidence from electronic devices.